Is It Germane to Sustain Higher Education Research in The Post-Covid-19 Era? - Odularu, Oluwayemi IbukunOluwa (Research in Social Sciences and Technology, 2024)
The COVID-19 pandemic has severely impacted developing countries, causing educational and economic crises globally. This study explores the necessity of maintaining research in Higher Education (HE) amidst the pandemic's disruptions. It questions whether Higher Education Institutions (HEIs) can sustain research post-COVID-19 while balancing essential functions to avoid risks. Despite extensive studies on HEIs' research sustainability post-pandemic, there is a notable gap in understanding the precise strategies needed to balance essential functions, address risks, and foster resilience amid uncertainties. To bridge this gap, the study highlights the importance of reassessing research priorities and methods in the changing HE landscape. A systematic literature review was conducted, gathering relevant literature from various databases. The study employed an exclusion and inclusion design for research selection. It points out that maintaining HE research post-pandemic has not been sufficiently investigated, leaving a critical gap in understanding research practices. The conceptual model, serving as the study's theoretical foundation, offers an organized means of evaluating the need for HE research considering the pandemic's global economic impacts. This study underscores the importance of multi-stage educational research in the post-COVID-19 era, given the interconnectedness of HEIs. It advocates for a flexible and dynamic research environment and suggests comprehensive approaches to anticipate and meet emerging trends in higher education. The study emphasizes that future research should focus on mitigating post-pandemic challenges and preparing for shifts in HE, promoting resilience and creativity in the field.